RRT*N: an efficient approach to path planning in 3D for Static and Dynamic Environments. (16th February 2021) - Mohammed, Hussein; Romdhane, Lotfi; Jaradat, Mohammad A.
ABSTRACT: In this paper, a modified algorithm of the Rapidly exploring Random Tree star (RRT*) is proposed. This method is called RRT*N. The main advantage of this method is its speed and robustness in finding the path to the target. An extension of this method to the 3D case is also presented and its capability of handling static obstacles and dynamic unknown moving obstacles in 2D and 3D environments, is shown. This improved method uses a probability distribution to generate new nodes. The nodes closest to the target have higher probability, which generates a tree centered on the line joining the robot to the target. It is shown that this method can be three times faster in finding the path to the target than the regular RRT* in the same environment. Simulation and experimental results are presented to show the robustness of the proposed RRT*N method. GRAPHICAL ABSTRACT: UF0001